Legal Implications of Unilateral Collateral Takeover by Village Credit Institutions on Debtors' Legal Protection - Parisnawati, Dewa Ayu M; Novitri, Egriel Cinta; Wijaya, Mahatma Mustika Purwa (Batulis Civil Law Review, 2026)
Introduction: Village Credit Institutions are community-based financial institutions with unique legal status in Bali, operating outside the jurisdiction of microfinance institutions. Village Credit Institutions when disbursing loans, often face bad loans, which are usually handled through the Blocking Mechanism (Taken Over Collateral). However, Taken Over Collateral is often carried out by the Village Credit Institution itself without the debtor's voluntary consent, which raises serious questions about the validity of the procedure and legal protection for the debtor. Purposes of the Research: This study discusses legal protection for debtors when Taken Over Collateral is applied unilaterally, judging from the principle of good faith, and also examines the legal consequences of such practices on the debtor's legal position. Methods of the Research: This research uses a normative approach with a legislative review, concepts, and historical approaches through the examination of primary, secondary, and tertiary legal materials. Results Main Findings of the Research: The results show that the Collateral Taken Over unilaterally is a violation of the principle of good faith because it was carried out without a valid voluntary surrender deed. The legal consequence is that the takeover has the potential to be null and void from the outset and can be canceled, as well as open up the possibility of lawsuits for unlawful acts. The debtor remains the legal owner of the guarantee until the execution is carried out procedurally and legally valid.